The Repertoire of Fos and Jun Proteins Expressed during the G(1) Phase of the Cell Cycle Is Determined by the Duration of Mitogen-Activated Protein Kinase Activation - Cook, Simon J. (American Society for Microbiology, 1999)
In Rat-1 fibroblasts nonmitogenic doses of lysophosphatidic acid (LPA) stimulate a transient activation of mitogen-activated protein kinase (MAPK), whereas mitogenic doses elicit a sustained response. This sustained phase of MAPK activation regulates cell fate decisions such as proliferation or differentiation, presumably by inducing a program of gene expression which is not observed in response to transient MAPK activation. We have examined the expression of members of the AP-1 transcription factor complex in response to stimulation with different doses of LPA. c-Fos, c-Jun, and JunB are induced rapidly in response to LPA stimulation, whereas Fra-1 and Fra-2 are induced after a significant lag. The expression of c-Fos is transient, whereas the expression of c-Jun, JunB, Fra-1, and Fra-2 is sustained. The early expression of c-Fos can be reconstituted with nonmitogenic doses of LPA, but the response is transient compared to that observed with mitogenic doses. In contrast, expression of Fra-1, Fra-2, and JunB and optimal expression of c-Jun are observed only with doses of LPA which induce sustained MAPK activation and DNA synthesis. LPA-stimulated expression of c-Fos, Fra-1, Fra-2, c-Jun, and JunB is inhibited by the MEK1 inhibitor PD098059, indicating that the Raf-MEK-MAPK cascade is required for their expression. In cells expressing a conditionally active form of Raf-1 (ΔRaf-1:ER), we observed that selective, sustained activation of Raf-MEK-MAPK was sufficient to induce expression of Fra-1, Fra-2, and JunB but, interestingly, induced little or no c-Fos or c-Jun. The induction of c-Fos observed in response to LPA was strongly inhibited by buffering the intracellular [Ca(2+)]. Moreover, although Raf activation or calcium ionophores induced little c-Fos expression, we observed a synergistic induction in response to the combination of ΔRaf-1:ER and ionomycin. These results suggest that kinetically distinct phases of MAPK activation serve to regulate the expression of distinct AP-1 components such that sustained MAPK activation is required for the induced expression of Fra-1, Fra-2, c-Jun, and JunB. However, in contrast to the case for Fra-1, Fra-2, and JunB, activation of the MAPK cascade alone is not sufficient to induce c-Fos expression, which rather requires cooperation with other signals such as Ca(2+) mobilization. Finally, the identification of the Fra-1, Fra-2, c-Jun, and JunB genes as genes which are selectively regulated by sustained MAPK activation or in response to activated Raf suggests that they are candidates to mediate certain of the effects of Ras proteins in oncogenic transformation.